Enantioselective endocrine disrupting effects of omeprazole studied in the H295R cell assay and by molecular modeling. (August 2016) - Sørensen, Amalie Møller; Hansen, Cecilie Hurup; Bonomo, Silvia; Olsen, Lars; Jørgensen, Flemming Steen; Weisser, Johan Juhl; Kretschmann, Andreas Christopher; Styrishave, Bjarne
Abstract: Enantiomers possess different pharmacokinetic and pharmacodynamic properties and this may not only influence the therapeutic effect of a drug but also its toxicological effects. In the present work we investigated the potential enantioselective endocrine disrupting effects of omeprazole (OME) and its two enantiomers on the human steroidogenesis using the H295R cell line. Differences in production of 16 steroid hormones were analyzed using LC–MS/MS. Additionally, to evaluate the differences in binding modes of these enantiomers, docking and molecular dynamics (MD) simulations of S -omeprazole ( S -OME) and R -omeprazole ( R- OME) in CYP17A1, CYP19A1 and CYP21A2 were carried out. Exposing H295R cells to OME and its enantiomers resulted in an increase of progesterone (PRO) and 17α-hydroxy-progesterone (OH-PRO) levels. At the same time, a decrease in the corticosteroid and androgen synthesis was observed, indicating inhibition of CYP21A2 and CYP17A1. In both cases, the effect of R -OME was smaller compared to that of the S- OME and a certain degree of enantioselectivity of CYP17A1 and CYP21A2 was suggested. Docking indicated that the N-containing rings of OME possibly could interact with the iron atom of the heme for S -OME in CYP17A1 and S- and R -OME in CYP21A2. However, density functional theory calculations suggest that the direct N-Fe interaction is weak. The study demonstrates enantioselective differences in the endocrine disrupting potential of chiral drugs such as omeprazole. These findings may have potential implications for drug safety and drug design. Highlights: The enantioselective effects of omeprazole were investigated in H295R cells and modeled in silico Omeprazole affected all steroids in the in vitro steroidogenesis by affecting CYP17 and CYP21 Enantioselective effects were observed in vitro for CYP21 and CYP17 In silico modeling indicates that CYP21 is the main target for the omeprazole enantiomers In silico modeling confirms the enantioselective effects on the CYP17